BS ISO 23132. Road vehicles. Extended Vehicle (ExVe) time critical applications. General requirements, definitions and classification methodology of time-constrained situations related to Road and ExVe Safety (RExVeS). (9th September 2019) - British Standards Institution,
No abstract available